Implementation of the Principles of Corporate Social Responsibility in Business Contract Law to Improve Community Welfare - Seri Wahyuni; Yuni Dhea Utari; Trisna Eka Sari; Melisa (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Abstract.  Corporate Social Responsibility (CSR) is becoming increasingly important in business, emphasizing a company's responsibility to society and the environment, in addition to financial profits. In the legal context of business agreements, CSR contributes to the welfare of society, especially in the era of globalization. In Indonesia, the implementation of CSR in business contract law is still new and not yet fully regulated, creating challenges related to protecting community rights and the social impact of business. This research explains that business agreement law encourages CSR through legal obligations, legal certainty, and facilitating cooperation between parties. Implementation of CSR principles in business agreements includes due diligence, environmental and worker rights clauses, as well as open communication with stakeholders. This increases public trust and corporate competitiveness, and supports sustainable development goals. The application of CSR in business contract law increases access to resources, community economic empowerment, and community quality of life, as well as minimizing negative environmental impacts. Thus, CSR contributes to sustainable development and the welfare of society as a whole. Use descriptive analysis methods with literature studies and document analysis.